Taking time: The temporal politics of dementia, care and support in the neighbourhood. Issue 9 (5th September 2022) - Ward, Richard; Rummery, Kirstein; Odzakovic, Elzana; Manji, Kainde; Kullberg, Agneta; Keady, John; Clark, Andrew; Campbell, Sarah
Abstract: Dementia is a global health challenge and currently the focus of a coordinated international response articulated through the notion of 'dementia‐friendly communities and initiatives' (DFCIs). Yet, while increasing research attention has been paid to the social and spatial dimensions to life with dementia in a neighbourhood setting, the temporalities of dementia have been largely overlooked. This article sets out different aspects of the lived experience of time for people with dementia and unpaid carers, before exploring the temporal politics of formal dementia care and support. The authors show that time is a site for material struggle and a marker of unequal relations of power. People with dementia and unpaid carers are disempowered through access to formal care, and this is illustrated in their loss of (temporal) autonomy and limited options for changing the conditions of the care received. The authors advocate for a time‐space configured understanding of the relationship with neighbourhood and foreground a tempo‐material understanding of dementia. Set against the backdrop of austerity policy in the UK, the findings reveal that ongoing budgetary restrictions have diminished the capacity for social care to mediate in questions of social justice and inequality, at times even compounding inequity.